Kinetic Systems: Jack Burnham and Hans Haacke - Chau, Christina (2014)
The following paper argues that Jack Burnham’s antipathy for kineticism in “Systems Esthetics” and Beyond Modern Sculpture has contributed to an assumption that kineticism is an obsolete practice “rooted in another age.” Contrary to Burnham, I argue that a focus on the kinetic movement in Hans Haacke’s sculptures is productive for establishing key understandings of systems theory in art. My interpretation of Haacke’s art emphasizes that movement in time is a key aspect of the artist’s approach to sytems theory, and is useful for making viewers conscious of the systems of perception at play when confronted with ontologically unstable works of art.